1984
DOI: 10.1677/joe.0.1020063
|View full text |Cite
|
Sign up to set email alerts
|

Release of oxytocin and vasopressin by magnocellular nuclei in vitro: specific facilitatory effect of oxytocin on its own release

Abstract: The release of endogenous oxytocin and vasopressin by rat paraventricular and supraoptic nuclei in vitro during a 10-min period, 30 min after beginning the incubation, was measured radioimmunologically. Mean basal hormone release per 10 min and per pair of nuclei was: 128.4 +/- 12.4 (S.E.M.) pg vasopressin (n = 15) and 39.0 +/- 3.0 pg oxytocin (n = 66) for supraoptic nuclei from male rats; 273.9 +/- 42.6 pg vasopressin (n = 11) and 34.2 +/- 3.5 pg oxytocin (n = 15) for supraoptic nuclei from lactating rats; 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
138
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(150 citation statements)
references
References 14 publications
(23 reference statements)
12
138
0
Order By: Relevance
“…As we used 10-12-week-old adult male mice, this PKC-and cADPR-dependent autoregulation of OT release is not related to female reproductive processes, but to social recognition or social behavior found in this mouse strain (Jin et al, 2007a;Liu et al, 2008). The positive feedback mechanism of OT release plays a critical and physiological role in causing uterus contraction during labor and triggering milk release from the breast tissue when infants are nursed (Moos et al, 1984;Neumann et al, 1994 and1996). A recent series of studies showed that nasal infusion of OT increases trust (Kosfeld et al, 2005), mind-reading (Domes et al, 2007), and generosity (Zak et al, 2007) in humans,…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As we used 10-12-week-old adult male mice, this PKC-and cADPR-dependent autoregulation of OT release is not related to female reproductive processes, but to social recognition or social behavior found in this mouse strain (Jin et al, 2007a;Liu et al, 2008). The positive feedback mechanism of OT release plays a critical and physiological role in causing uterus contraction during labor and triggering milk release from the breast tissue when infants are nursed (Moos et al, 1984;Neumann et al, 1994 and1996). A recent series of studies showed that nasal infusion of OT increases trust (Kosfeld et al, 2005), mind-reading (Domes et al, 2007), and generosity (Zak et al, 2007) in humans,…”
Section: Discussionmentioning
confidence: 95%
“…Locally released OT in the brain causes excitation of OT neurons by activating OT receptors, a class A family (2.1:OXY:1:OT: in IUPHA data base; http://www.iuphar-db.org/GPCR/ReceptorListForward?class=class%20A), expressed on both neurons of the PVN and SON and nerve endings in the posterior pituitary (Adan et al, 1995;Freund-Mercier et al, 1994;Young et al, 1997). This excitation leads to facilitative OT release, known as autoregulation (Moos et al, 1984;Neumann et al, 1996). The autoregulation of OT-induced OT release occurs during uterine contraction in labor and milk ejection in lactation (Richard et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Present data also show that the systemic injection of oxytocin to the PO7 neonatal as well as to the adult male rat induces the immediate activation of ejaculatory rhythmic motor patterns, suggesting that the spinal oxytocinergic system is involved in the functioning of the spinal generator for ejaculation. In the adult male rat, it has been demonstrated that the source of oxytocin for the spinal cord is the hypothalamus, 18 and that electrical stimulation of the posterior hypothalamic area produces the release of important amounts of this peptide; 19 however, an endogenous source of oxytocin in the neonatal spinal cord has not been described. Thus, it is necessary to perform specific experiments to further examine the developmental organization and functioning of the spinal oxytocinergic system and its relation to ejaculation across postnatal development.…”
Section: Discussionmentioning
confidence: 99%
“…This increase was directly related to the distal release of hormone and more precisely, the increase in exocytosis (26). Exocytosis (27) and VP release (28,29) also occur at central level for vasopressinergic neurons. This central release…”
Section: Discussionmentioning
confidence: 99%